Ekologi dan Ekoteologi dalam Perspektif Hadis Tarbawi - Navira Riska Fathana; Rizka Fadhilah Nasution; Zuhriana Humairoh; Dwi Meutia Hasni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The world today is facing a serious ecological crisis stemming from a moral crisis and an exploitative anthropocentric paradigm, making it necessary to establish a strong foundation for environmental education based on spiritual values. This study aims to examine ecological and eco-theological paradigms from the perspective of educational hadith to provide a theoretical contribution to the development of character education focused on environmental care. The method used is a qualitative approach involving library research, which analyzes primary and secondary documents from reputable national and international scientific articles. The research findings indicate that eco-theology in the hadith positions humans as khalifah fil ardh entrusted with the responsibility to maintain ecological balance (tawazun). Environmental conservation ethics from the hadith perspective encompass the obligation to maintain cleanliness, the prohibition against causing damage through the exploitation of arid lands, and the principle of efficient water resource use, as exemplified by the Prophet Muhammad ﷺ. In conclusion, environmental conservation is an integral part of faith that must be integrated into the cognitive, affective, and psychomotor domains of modern education. Islam offers preventive theological-educational solutions to cultivate individuals with ecological piety for the sustainability of the global ecosystem.